Pergerakan Islam dan Demokrasi di Indonesia - Muhamad Shadiq, Gusti; Hasan, Ahmadi; Umar, Masyithah; Khasyi'in, Nuril (PT. Sharia Journal and Education Center, 2024)
Abstract This research discusses the relationship between the movement of Islam and democracy in Indonesia, as well as how these two concepts influence and contribute to the country's social and political development. Although democracy is not explicitly mentioned in the Qur'an or Hadith, the principles of democracy are substantially reflected in Islamic teachings such as equality, deliberation (shura), cooperation (ta'awun), and good practices (taghyir). The experiences of Prophet Muhammad also provide an ethical and moral foundation that correlates with the basic principles of modern democracy. These Islamic values have become an integral part of Indonesia's constitution, including Pancasila and various laws governing the principles of democracy and divinity. Islam holds an important position in the Indonesian government, reflecting the majority Muslim population and the historical struggle for independence closely linked with the Muslim community. The influence of Islamic values in the Indonesian constitution has been achieved through the active participation of Indonesian Muslims in the democratization process, demonstrating that Islam and democracy can support each other and are not mutually exclusive. The conclusion of this research emphasizes that the integration of Islamic teachings and state policies is key to the success of democracy in Indonesia, avoiding conflict and strengthening harmony in national and state life.Keywords: khilafah, paragidma, fundamental, moderate, liberal. Keywords: Islam, Democracy, Indonesia, Constitution, Deliberation Abstrak Penelitian ini membahas hubungan antara pergerakan Islam dan demokrasi di Indonesia, serta bagaimana kedua konsep tersebut saling mempengaruhi dan berkontribusi terhadap pembangunan sosial dan politik negara. Meskipun secara tekstual demokrasi tidak disebutkan dalam Al-Qur’an atau Hadits, prinsip-prinsip demokrasi secara substansial tercermin dalam ajaran Islam seperti kesetaraan, musyawarah (syura), kerjasama (ta’awun), dan kebiasaan baik (taghyir). Pengalaman Nabi Muhammad juga memberikan landasan etika dan moral yang berkorelasi dengan prinsip-prinsip dasar demokrasi modern. Nilai-nilai Islam ini kemudian menjadi bagian integral dari konstitusi Indonesia, termasuk Pancasila dan berbagai undang-undang yang mengatur prinsip-prinsip demokrasi dan ketuhanan. Islam menempati posisi penting dalam pemerintahan Indonesia, mencerminkan mayoritas penduduk yang beragama Islam dan sejarah perjuangan kemerdekaan yang erat kaitannya dengan umat Islam. Pengaruh nilai-nilai Islam dalam konstitusi Indonesia dicapai melalui partisipasi aktif umat Islam dalam proses demokratisasi, yang menunjukkan bahwa Islam dan demokrasi dapat saling mendukung dan tidak saling bertentangan. Kesimpulan dari penelitian ini menegaskan bahwa integrasi antara ajaran Islam dan kebijakan negara adalah kunci keberhasilan demokrasi di Indonesia, menghindari konflik dan memperkuat harmoni dalam kehidupan berbangsa dan bernegara.. Kata Kunci: Islam, Demokrasi, Indonesia, Konstitusi, Musyawarah